2020
DOI: 10.3390/ma13132905
|View full text |Cite
|
Sign up to set email alerts
|

Axial Behavior of Reinforced UHPC-NSC Composite Column under Compression

Abstract: This paper proposes a novel reinforced ultra-high-performance concrete (UHPC)-normal strength concrete (NSC) composite column. The main feature of the reinforced UHPC-NSC composite column is the use of an exterior UHPC cover, which is helpful for improving the load-carrying capacity, deformability, and crack resistance. This study focused on the axial behavior of the reinforced UHPC-NSC composite column. A total of 12 specimens were designed to investigate the axial behavior of the composite column under compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Lu et al (2021) [12] found that among the components of UHPC, the water-binder ratio had the greatest influence on frost resistance. Li et al (2020) [13] found that the damage of the chloride salt freeze-thaw cycle to reactive powder concrete (RPC) was greater than that of the freshwater freeze-thaw cycle. Zhang et al (2020) [14] found that freeze-thaw cycles accelerated the development of cracks in ordinary reinforced concrete (RC) columns, and the number of cracks increased with the increase of F-T times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al (2021) [12] found that among the components of UHPC, the water-binder ratio had the greatest influence on frost resistance. Li et al (2020) [13] found that the damage of the chloride salt freeze-thaw cycle to reactive powder concrete (RPC) was greater than that of the freshwater freeze-thaw cycle. Zhang et al (2020) [14] found that freeze-thaw cycles accelerated the development of cracks in ordinary reinforced concrete (RC) columns, and the number of cracks increased with the increase of F-T times.…”
Section: Introductionmentioning
confidence: 99%
“…Xie [20] found that the axial compressive bearing capacity of UHPC-RC composite columns gradually increased with the increase in UHPC tube thickness. Li [21] found that the bearing capacity of the composite column of pouring the concrete core first and pouring the UHPC tube later is higher than that of pouring the UHPC tube first and pouring the core concrete later. Zhang [22] and Shan [23] found that increasing the steel fiber content and stirrup ratio of UHPC tubes can effectively improve the peak load and ductility of UHPC-RC composite columns.…”
Section: Introductionmentioning
confidence: 99%
“…The UHPFRC gains interest in research covering column strengthening due to the properties mentioned, providing superior resistance capacity for the original structure without a significant increase in the thickness of the system 23 . As a result, a series of investigations were conducted on the performance of column strengthened using the UHPFRC 23–26 …”
Section: Introductionmentioning
confidence: 99%
“…Li et al 26 studied 12 examples of columns with layers of high‐performance concrete with longitudinal and transverse reinforcement rebar. The authors investigated some parameters: the jacketing thickness, the volumetric ratio of stirrups, and the construction method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation